ANALISIS PERAN SERTA PEMAHAMAN E-COMMERCE BAGI SUMBER DAYA MANUSIA DALAM MENGEMBANGKAN PERBANKAN BERBASIS SYARIAH DI INDONESIA - Harry Wihartanto Sudewo; Sumadi; Sri Walyoto; Agus Marimin (Jurnal Ilmiah Ekonomi Islam, 2026)
Provides an illustration that related to the development of sharia banking requires active marketing based on information technology that is capable of introducing and expanding the network of sharia banking products in the community. Regulation of the Financial Services Authority of the Republic of Indonesia Number 11/POJK.03/2022 concerning the Implementation of Information Technology by Commercial Banks. Related to this, e-commerce or in the Indonesian dictionary means Electronic Commerce or e-commerce is all buying and selling activities or transactions carried out using electronic media (the internet). Even though telephones and television are included as electronic means, e-commerce now refers more to digital technology or the internet. This is a challenge in itself for sharia-based economic actors, especially sharia banking, in following developments in information technology that are in accordance with the basic principles of the sharia economy itself. As well as innovative human resources and knowledge of information technology that can be used in introducing and obtaining active marketing related to sharia-based banking products themselves.